Influence of in situ micro-rolling on the improved strength and ductility of hybrid additively manufactured metals. (August 2021) - Hu, Yanan; Ao, Ni; Wu, Shengchuan; Yu, Yukuang; Zhang, Haiou; Qian, Weijian; Guo, Guangping; Zhang, Mingbo; Wang, Guilan
Highlights: Both the tensile strength and ductility of the HRAM-processed alloy are improved. The HRAM-processed alloy is characterized by a high dislocation density and large α laths. High dislocation density and large α laths lead to the improved strength and ductility, respectively. The fatigue crack growth resistance of HRAM-processed alloy is isotropic. Abstract: Hybrid in situ rolled wire + arc additive manufacturing (HRAM) is a novel printing technology capable of fabricating large-scale components by combining in situ micro-rolling with standard wire + arc additive manufacturing (WAAM), which enhances the ductility and tensile strength of the resulting parts. This study attempts to identify the aspects of the microstructure that are critical to the property improvement. The microstructure of the WAAM- and HRAM-processed Ti6Al4V alloys exhibited a basketweave morphology composed of α laths and β phases. The HRAM-processed alloy was characterized by a higher dislocation density and larger α laths compared to those of the WAAM-processed alloy. The relatively high dislocation density and large α laths are responsible for the improvement in the tensile strength and ductility, respectively. The spatial evolution of cracking for the HRAM-processed alloy was investigated using a specially designed uniaxial tension/compression rig mounted on the synchrotron X-ray computed microtomography platform. The failure originated from the nucleation of micro voids and surface cracks.